2008
DOI: 10.2225/vol11-issue2-fulltext-8
|View full text |Cite
|
Sign up to set email alerts
|

Induction of in vitro flowering in Capsicum frutescens under the influence of silver nitrate and cobalt chloride and pollen transformation

Abstract: The influence of silver nitrate (AgNO 3 ) and cobalt chloride (CoCl 2 ) on shoot multiplication and in vitro flowering in Capsicum frutescens Mill. was investigated. Exogenous administration of AgNO 3 and CoCl 2 at a concentration of 30 µM resulted in the maximum tissue response in terms of shoot length and number of shoots after 45 days culturing on MS medium. Both silver nitrate (40 µM) and cobalt chloride (30 µM) influenced in vitro flowering after 25 and 45 days respectively. This is the first report on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 10 publications
0
27
0
2
Order By: Relevance
“…However in pollen obtained from the in vitro flowers of C. frutescens inoculated with A. tumefaciens was observed transient GUS expression (Sharma et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…However in pollen obtained from the in vitro flowers of C. frutescens inoculated with A. tumefaciens was observed transient GUS expression (Sharma et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…In Echinacea angustifolia, 1 mg L -1 CoCl 2 promoted shoot regeneration, whereas higher CoCl 2 concentrations (5-20 mg L -1 ) decreased shoot multiplication percentage, number of shoots per explant, and shoot length . In Capsicum frutescens Mill., exogenous administration of 30 µM CoCl 2 resulted in the maximum tissue response in terms of shoot length and number of shoots after 45 days of culturing on MS medium (Sharma et al, 2008). In tomato, on the other hand, CoCl 2 resulted in a significant decrease of shoot fresh and dry weight (Hasan et al, 2011 Ethylene inhibitor type (A) 0.000 *** 0.000 *** 0.000 *** 0.008 ** Ethylene inhibitor conc.…”
Section: Discussionmentioning
confidence: 99%
“…In barley cultivar Morex, almost doubled regeneration was recorded using AgNO3, while 1.5-folds for Golden Promise (Jha et al 2007). Moreover, addition of AgNO3 increased the frequency of plant regeneration significantly in various plants species such as Pearl millet (Oldach et al 2001), Naga chilli (Bora et al 2014, Sharma et al 2008), wheat (Bouiamrine et al 2012, Wu et al 2006, maize (El-Itriby et al 2003, Huang et al 2004, sorghum (Pola et al 2009). In our investigation around 27-folds higher regeneration was recorded in 1.5 mg/l AgNO3 and 150 mg/l L-glutamine for BARI barley-6.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some reports have been mentioned that use of silver nitrate (AgNO3) and/ or amino acids in media, plays an important role to improve callus induction, shoot and root formation in various plants; such as wheat (Wu et al 2006, Bouiamrine et al 2012, maize (El-Itriby et al 2003), sorghum (Pola et al 2009), pearl millet (Oldach et al 2001 and Naga chilli (Sharma et al 2008, Bora et al 2014. Some authors also reported that regeneration can be improved by AgNO3 in both dicots and monocots (Kumar et al 2009, Kabir et al 2013.…”
Section: Introductionmentioning
confidence: 99%